Penerapan Konsep Pale Blue Dot Dalam Rancangan Bentuk Planetary Center - Cintya, Anindita; Hendra, Failasuf Herman; Salisnanda, Randy Pratama (Institut Teknologi Adhi Tama Surabaya, 2023)
Planetarium as educational tourism is a building that presents star shows in a unique dome building, with a museum and observation area as additional facilities. In Indonesia itself, several planetariums are spread across several regions, from simple ones, to planetary with real-time star observation facilities.At the Planetary Center, visitors are like being in an imaginary space that develops various other facilities such as education, interactive museums, and collaborative projects. The design aims to describe the boundaries, uniqueness and beauty of outer space and its planets.Apart from facilities, the shape and facade of the building also have an important role in attracting interest and maintaining people's enthusiasm for returning visits. With a Futuristic Architecture theme approach, the Planetary Center takes the idea of Pale Blue Dot as the macro concept and Planet Earth as the micro concept of the building. Because the idea for the concept itself originates from space, the Pale Blue Dot concept becomes an important point on the building facade as the identity of the Planetary Center.